2008
DOI: 10.1103/physrevlett.101.010502
|View full text |Cite
|
Sign up to set email alerts
|

Measurement-Based Quantum Computer in the Gapped Ground State of a Two-Body Hamiltonian

Abstract: We propose a scheme for a ground-code measurement-based quantum computer, which enjoys two major advantages. First, every logical qubit is encoded in the gapped degenerate ground subspace of a spin-1 chain with nearest-neighbor two-body interactions, so that it equips built-in robustness against noise. Second, computation is processed by single-spin measurements along multiple chains dynamically coupled on demand, so as to keep teleporting only logical information into a gapprotected ground state of the residu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
257
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(257 citation statements)
references
References 22 publications
(27 reference statements)
0
257
0
Order By: Relevance
“…As originally proposed in Ref. [11] as the ground-code version of MQC using coupled 1D AKLT states, if we are capable of adiabatically turning off a two-body interacting term only to the spin to be measured selectively -importantly that still does not have to create new entanglement -we could indeed make the Hamiltonian in the remaining bulk coexist without interfering the MQC protocol for quantum computation. Then, the Hamiltonian with a (conjectured) gap would be able to contribute to a passive protection of the logical information stored in the degenerate ground state, by providing some robustness against local noises, in compared to a scenario where the bulk Hamiltonian is absent.…”
Section: Ground-code Mqcmentioning
confidence: 99%
See 2 more Smart Citations
“…As originally proposed in Ref. [11] as the ground-code version of MQC using coupled 1D AKLT states, if we are capable of adiabatically turning off a two-body interacting term only to the spin to be measured selectively -importantly that still does not have to create new entanglement -we could indeed make the Hamiltonian in the remaining bulk coexist without interfering the MQC protocol for quantum computation. Then, the Hamiltonian with a (conjectured) gap would be able to contribute to a passive protection of the logical information stored in the degenerate ground state, by providing some robustness against local noises, in compared to a scenario where the bulk Hamiltonian is absent.…”
Section: Ground-code Mqcmentioning
confidence: 99%
“…This seems to be the reason why MQC on the 2D AKLT state has been an open question in a long time, although the AKLT state by the 1D spin-1 chain was shown in Ref. [11] to be capable of simulating a single quantum wire of MQC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One might expect that one or more of these properties would be necessarily satisfied by any universal resource state. This has turned out not to be the case; several authors in recent years have identified resources that differ materially from the cluster states [4,5,[9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they are unique ground states of two-body interacting Hamiltonians with suitable boundary conditions. Even though quantum computational universality in MBQC requires at least a 2D structure, the results on the 1D spin-1 AKLT state for theoretically and experimentally simulating one-qubit gates [11,27,28] prompted the quest of universality in 2D AKLT states. However, the capability of full quantum computational universality was only established recently in the spin-3/2 AKLT state on the honeycome lattice [29,30] and later on some other trivalent lattices [31], as well as some lattices that host spin-2 and other lower spin (such as spin-3/2 or spin-1) hybrid AKLT states [32].…”
Section: Introductionmentioning
confidence: 99%